2013
DOI: 10.1371/journal.pone.0065533
|View full text |Cite
|
Sign up to set email alerts
|

Non-Smoking Male Adolescents' Reactions to Cigarette Warnings

Abstract: BackgroundThe U.S. Food and Drug Administration (FDA) is working to introduce new graphic warning labels for cigarette packages, the first change in cigarette warnings in more than 25 years. We sought to examine whether warnings discouraged participants from wanting to smoke and altered perceived likelihood of harms among adolescent males and whether these warning effects varied by age.MethodsA national sample of 386 non-smoking American males ages 11–17 participated in an online experiment during fall 2010. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 21 publications
1
41
1
Order By: Relevance
“…Evoked fear is found to have a stronger effect than beliefs in mediating the effects of GHWs on quit thoughts for adolescent smokers, yet this is reversed in a longitudinal study of young adult smokers. A recent examination of male, adolescent nonsmoker data (Pepper et al, 2013) reveals that the GHWs discouraged most male adolescents from wanting to smoke, but lung cancer warnings discouraged them more than addiction warnings. Finally, moderators can have an important impact on the effectiveness of the GHWs.…”
Section: Cigarettes and Graphic Health Warningsmentioning
confidence: 99%
“…Evoked fear is found to have a stronger effect than beliefs in mediating the effects of GHWs on quit thoughts for adolescent smokers, yet this is reversed in a longitudinal study of young adult smokers. A recent examination of male, adolescent nonsmoker data (Pepper et al, 2013) reveals that the GHWs discouraged most male adolescents from wanting to smoke, but lung cancer warnings discouraged them more than addiction warnings. Finally, moderators can have an important impact on the effectiveness of the GHWs.…”
Section: Cigarettes and Graphic Health Warningsmentioning
confidence: 99%
“… 10 15–21 However, while some studies find that smokers and non-smokers rate pictorial warnings as more effective than text-only warnings, 22–26 other studies have reported conflicting findings. 27–29 For instance, studies have found that graphic, pictorial warnings result in poorer recall than less graphic or non-graphic warnings, 28 do not increase youth's expectations to be non-smokers a year later, 29 have no effect on beliefs about cancer or addiction among non-smoking adolescent boys, 26 and are effective in lowering smoking intentions for Canadians but not for Americans. 27 …”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have yielded mixed findings among adolescents. For example, several studies have found pictorial warnings engendered higher perceived effectiveness and quit intentions than text warnings [1012], whereas others showed no difference in discouragement from smoking [13] or demonstrated higher intentions to smoke in response to pictorial warnings [12]. However, each of these studies relied on brief exposures to warnings in artificial settings.…”
mentioning
confidence: 99%